The enhancement of driver seat comfort for small size car: a preliminary study - N. S. M., Noor; Z., Ghazalli; R., Mamat; K., Kadirgama; M. S. M., Sani; Z., Ahmad; Nasrul Hadi, Johari (Malaysian Public Health Physicians’ Association, 2016)
Seating comfort is one of the important indicators while driving especially for a long hour drive. The objective of this study was to execute a preliminary study of survey and identify the discomfort of body while driving and after driving session by conductinga survey. The questionnaire developed was tested for its reliability. By using Cronbach’s Alpha, this paper’s contribution was found to be significant in which it provides a survey with acceptable test reliability in which the alpha (α) was 0.887. The survey was conducted on 30 students of University Malaysia Pahang (20 male and 10 female) with driving experience and valid driving license. The subjects should have experiences in driving small size car or mini car as well. The results showed that the body area that the drivers felt discomfort while driving and after driving should be known. The findings showed that the discomfort was intense at the neck, upper back, and lumbar while and after driving.